RBC Response in Mice to Low Level Gamma Irradiation and Their Protection by Liv 52 - Waghmare, Girish (International Journal of Pharmaceutical & Biological Archive, 2013)
RBC Response in Mice to Low Level Gamma Irradiation and Their Protection by Liv 52